Benefit of electrocardiography during front-line combination paclitaxel and carboplatin chemotherapy for epithelial ovarian cancer - Kietpeerakool C. (2014)
Objective: To evaluate the patterns of electrocardiography (ECG), cardiac risk factors and its clinical consequence in women with epithelial ovarian cancer (EOC) who received paclitaxel and carboplatin (PC) as front line chemotherapy Material and Method: The medical records and electrocardiographic data of women with EOC who received paclitaxel (175 mg/m2) and carboplatin (AUC = 5) every 3 weeks at Chiang Mai University Hospital between January 2000 and December 2004 were reviewed for cardiac risk factors and clinical consequence. Results: Among 79 women receiving PC for EOC, 43 (54.4%) had cardiac risk factors. Seventy (88.6%) women had normal ECG, the remaining nine had sinus tachycardia (5), bundle branch block (2), mild T inversion (1), and Wolff-Parkinson-White syndrome (1) before the first course of chemotherapy. Among 70 women with normal initial ECG, 8(11.4%) had sinus tachycardia, one(1.4%) had early depolarization, two (2.9%) had sinus bradycardia and three (4.3%) had sinus arrhythmia in subsequent ECG. All these cardiac disturbances were asymptomatic and needed no intervention, indicating grade 1 toxicity. The odds ratio of developing abnormal ECG in women with cardiac risk factor was 1.24(95%CI = 0.33 to 4.64, p = 0.77). Among nine patients with abnormal ECG before the first course of PC, six (66.7%) had subsequent abnormal ECG but all were asymptomatic and no worsening of abnormal ECG pattern was noted. Conclusion: Although paclitaxel and carboplatin chemotherapy could induce abnormal ECG in women with either normal or abnormal prior ECG, its consequence was of no clinical significance. Therefore, the benefit of ECG before each treatment course was theoretically limited.